Plato and ‘the Birdhunters’: The Controversial Legacy of an Elusive Swan - Motta, Anna (Peitho. Examina Antiqua, 2015)
The aim of this paper is to discuss some features of the doctrines of the agrapha dogmata in Neoplatonism, starting from the reading of an anecdote, presented in the Anonymous Prolegomena to Platonic Philosophy, in which Plato dreams that close to death he becomes a swan which hunters are unable to catch. In fact, the dream is an explanation of the development of the Platonic tradition, and, more precisely, it presents a story of several exegetical disagreements that have survived till the present day. Compared to modern interpretation of the Aristotelic testimony on the “so-called unwritten doctrines”, we can state that the late antique interpretations of them focus and depend on what Plato has left us in his written dialogues, which are the best living images of his oral dialogues. This conclusion is, then, a consequence of a study carried out on Ancient and Neoplatonic texts that leads to the acknowledgement of a Platonic philosophical system as well as to an overview of modern secondary bibliography produced by the esoteric interpretation of Plato and various views of scholars who are against this account.